PENGARUH ECONOMIC VALUE ADDED TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ( BEI ) PERIODE 2010 – 2014 - Dessy Kemala; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed to analyze the influence of Economic Value Added on stock prices at food and beverage’s sub sector industry listed in Indonesia Stock Exchange ( IDX ) period 2010 – 2014 . This research used financial ratio analysis, it was Economic Value Added. The method to observe the effect of Economic Value Added on stock prices was simple linear regression of stastical analysis. Analysis data using simple linear regression , t test , and coefficient of determination test.The result showed that the Economic Value Added variable partially affect significantly againts the price of share in food beverage industry that are listed in Indonesia Stock Exchange (IDX).Keywords : Economic Value Added, Stock Prices